The Protective Effect of Ubiquinone against the Amyloid Peptide in Endothelial Cells Is Isoprenoid Chain Length-Dependent - Javier Frontiñán-Rubio; Yoana Rabanal-Ruiz; Mario Durán-Prado; Francisco Javier Alcain (MDPI AG, 2021)
Vascular brain pathology constitutes a common feature in neurodegenerative diseases that could underlie their development. Indeed, vascular dysfunction acts synergistically with neurodegenerative changes to exacerbate the cognitive impairment found in Alzheimer's disease. Different injuries such as hypertension, high glucose, atherosclerosis associated with oxidized low-density lipoprotein or inflammation induce NADPH oxidase activation, overproduction of reactive oxygen species, and apoptosis in endothelial cells. Since it has been shown that pretreatment of cultured endothelial cells with the lipophilic antioxidant coenzyme Q10 (CoQ10) displays a protective effect against the deleterious injuries caused by different agents, this study explores the cytoprotective role of different CoQs homologues against Aβ25-35-induced damage and demonstrates that only pretreatment with CoQ10 protects endothelial brain cells from Aβ25-35-induced damage. Herein, we show that CoQ10 constitutes the most effective ubiquinone in preventing NADPH oxidase activity and reducing both reactive oxygen species generation and the increase in free cytosolic Ca2+ induced by Aβ25-35, ultimately preventing apoptosis and necrosis. The specific cytoprotective effect of CoQ with a side chain of 10 isoprenoid units could be explained by the fact that CoQ10 is the only ubiquinone that significantly reduces the entry of Aβ25-35 into the mitochondria.